A new limestone-dwelling Four-clawed Gecko from Sa Kaeo Province, eastern Thailand (Squamata, Gekkonidae: Gehyra) - Meesook, Worawitoo; Donbundit, Nattasuda; Jindamad, Tanasak; Topai, Nittaya; Kunya, Kirati; Suthanthangjai, Winai; Suthanthangjai, Maneerat; Chotjuckdikul, Natthaphat; Chonkamnord, Teeraphat; Sumontha, Montri; Pauwels, Olivier S. G. (Zootaxa, 2025)
We describe Gehyra shiva sp. nov. from limestone cave and hills in Khlong Hat District, Sa Kaeo Province, eastern Thailand, near the border with Cambodia. The new species differs from all currently recognized Southeast Asian Gehyra by the following combination of morphological characters and dorsal color pattern: maximal known snout–vent length of 53.8 mm, 8–10 supralabials, 54–67 dorsal and 46–56 ventral scale rows around midbody, absence of skin folds on limbs, 34–37 preanofemoral pores in males in a continuous series extending along the whole length of the femur (pores absent in females), tail not to moderately widened behind vent in adults, a single row of widened subcaudals, digits and toes unwebbed, 7 or 8 divided subdigital lamellae on 4th toe, and a dorsal pattern with five regular dark brown bands between limb insertions, separated or not by pairs of large, white round paravertebral spots.